Behbudi and Munavvari's Contributions to the Development of Jadid Primary Schools (Journal of Pedagogical Inventions and Practices, 2022)
This article shows that in Turkestan during the national awakening, enlightened educators Behbudi and Munavvarqari had a great contribution to the establishment of new schools, the introduction of new teaching methods and the training of a large group of teachers. and it speaks of the courage he showed in shaping and developing these schools.